2015
DOI: 10.1353/bsr.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

The Exploration of Theater as Innovative Tool to Improve hiv Rates Among Black Men

Abstract: The current study assessed the impact of theater, as a health education intervention, upon knowledge of risk factors that contribute to hiv/aids and sexually transmitted infections among black males. Participants (n = 124) were given measures to assess their hiv/aids knowledge and sexual behavior before and after the play "Lonely Words". Paired sample t-tests were used to investigate mean differences in the responses for each of the items on both the knowledge and behavior scales. Results indicated that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Theater as a tool to educate African-American communities about cancer-related issues is an effective means of eliciting health conscious behavioral change and increasing positive health outcomes [19]. A study conducted by Cameron et al on prostate cancer among southern African-American men found theater to be effective in increasing prostate cancer knowledge, the likelihood of men engaging in healthier behaviors, and reporting of prostate screening [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theater as a tool to educate African-American communities about cancer-related issues is an effective means of eliciting health conscious behavioral change and increasing positive health outcomes [19]. A study conducted by Cameron et al on prostate cancer among southern African-American men found theater to be effective in increasing prostate cancer knowledge, the likelihood of men engaging in healthier behaviors, and reporting of prostate screening [14].…”
Section: Introductionmentioning
confidence: 99%
“…After viewing the play, participants reported having increased empathy and understanding of the disease [16]. Theater has also proven to be effective in increasing HIV/AIDS knowledge and encouraging healthier sexual behavior among young African Americans [19].…”
Section: Introductionmentioning
confidence: 99%